Prospective evaluation of inappropriate unable-to-assess CAM-ICU documentations of critically ill adult patients. Issue 1 (December 2015) - Terry, Kimberly; Anger, Kevin; Szumita, Paul
Abstract Background Delirium occurs in the intensive care unit and identification is often performed using a validated assessment tool such as the Confusion Assessment Method for Intensive Care Unit (CAM-ICU) patients. The CAM-ICU has three ratings: positive, negative, and unable to assess (UTA). Patients may often be assigned UTA when it is inappropriate given the level of sedation or medical condition. The purpose of this study is to evaluate the rate of inappropriate UTA CAM-ICU documentations. Methods A single-center prospective observational analysis was performed evaluating CAM-ICU documentations from October 27, 2014, to December 26, 2014. Patients admitted to the medical and surgical ICU were included and excluded if admitted to the ICU for less than 24 h. CAM-ICU assessments were performed per institutional guidelines using CAM-ICU scoring as validated in literature. CAM-ICU patient documentations were recorded as positive, negative, UTA, or not assessed. Patients with an appropriate UTA documentation were deeply sedated, non-English speaking, or not medically able to participate in the assessment. The major endpoint assessed rates of inappropriate UTA CAM-ICU documentations. Minor endpoints evaluated adherence to CAM-ICU documentations and use of pharmacologic agents for symptoms of delirium. Results Sixty-one patients were identified with 45 (74 %) medical, 16 (26 %) surgical, of which 27 (44.3 %) were mechanically ventilated. There were 116 UTA documentations with 35 (30.2 %) identified as inappropriate. Of the 906 identified CAM-ICU documentation opportunities, adherence was 439 (48.5 %). Overall, 18 (29.5 %) of the 61 patients were administered pharmacologic agents for delirium management and 5 (27.7 %) had a positive CAM-ICU documented within 24 h. Conclusions Rates of inappropriate UTA CAM-ICU documentations may be significantly higher than reported in literature. Additional research is needed to identify an acceptable rate of inappropriate UTA CAM-ICU assessments and its clinical impact on delirium management.